Enhanced visualization of mobile chest X-ray images in the intensive care setting using software scatter correction. (February 2023) - Targett, Harry; Hutchinson, Dominic; Hartley, Richard; McWilliam, Richard; Lopez, Ben; Crone, Ben; Bonner, Stephen
Background: Mobile chest X-ray (CXR) scans are performed within intensive treatment units (ITU) without anti-scatter grids for confirming tube and line hardware placement. Assessment is therefore challenging due to degraded subject contrast resulting from scatter. Purpose: To evaluate the efficacy of a software scatter correction method (commercially named Trueview) for enhanced hardware visualization and diagnostic quality in the ITU setting. Material and Methods: A total of 30 CXR scans were processed using Trueview and compared with standard original equipment manufacturer (OEM) images via observer scoring study involving two radiology and four ITU doctors to compare visualization of tubes and lines. Results were analyzed to determine observer preference and likelihood of diagnostic quality. Results: Reviewers were more likely to score Trueview higher than OEM for mediastinal structures, bones, retrocardiac region, tube visibility, and tube safety ( P < 0 . 01). Visual grading characteristic analysis suggested a clinical preference for Trueview compared with OEM for mediastinal structures (area under the visual grading characteristic curve [AUCVGC ] = 0.60, 95% confidence interval [CI] = 0.55–0.65), bones (AUCVGC = 0.61, 95% CI = 0.55–0.66), retrocardiac region (AUCVGC = 0.64, 95% CI = 0.59–0.69), tube visibility (AUCVGC = 0.65, 95% CI = 0.60–0.70), and tube safety (AUCVGC = 0.68, 95% CI = 0.64–0.73). Reviewers were indifferent to visualization of the lung fields (AUCVGC = 0.49, 95% CI = 0.44–0.55). Registrars (3/6 reviewers) were indifferent to the mediastinal structure regions (AUCVGC = 0.54, 95% CI = 0.47–0.62). Conclusion: Reviewers were more confident in identifying the placement and safety of tubes and lines when reviewing Trueview images than they were when reviewing OEM.